Haplotype Analysis of Varroa destructor and Deformed Wing Virus Using Long Reads - Bai, Wen Feng; Lin, Zhe Guang; Yan, Wei Yu; Zhang, Li Zhen; Evans, Jay D.; Huang, Qiang (Frontiers in Insect Science, 2021)
As a phoretic parasite and virus vector, the mite Varroa destructor and the associated Deformed wing virus (DWV) form a lethal combination to the honey bee, Apis mellifera. Routine acaricide treatment has been reported to reduce the diversity of mites and select for tolerance against these treatments. Further, different DWV strains face selective pressures when transmitted via mites. In this study, the haplotypes of Varroa mites and associated DWV variants were quantified using long reads. A single haplotype dominated the mite mitochondrial gene cytochrome oxidase subunit I, reflecting an ancient bottleneck. However, highly polymorphic genes were present across the mite genome, suggesting the diversity of mites could be actively maintained at a regional level. DWV detected in both mites and honey bees show a dominant variant with only a few low-frequency alternate haplotypes. The relative abundances of DWV haplotypes isolated from honey bees and mites were highly consistent, suggesting that some variants are favored by ongoing selection.